1976
DOI: 10.1037/0022-006x.44.3.363
|View full text |Cite
|
Sign up to set email alerts
|

Childhood roots of schizophrenia.

Abstract: Earlier project reports compared childhood social behavior of nonmigratory schizophrenics and normal classmates by analyzing teachers' comments in school records. This article expands the sample to include migratory schizophrenics and analyzes childhood intellectual functioning. Behavioral differences indicated emotional immaturity and social alienation in the preschizophrenics, with sharp sex differences. Preschizophrenic boys were abrasive and antisocial, whereas prcschizophrenic girls were introverted and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 18 publications
(8 reference statements)
3
63
0
1
Order By: Relevance
“…There have been suggestions that female children who develop schizophrenia in the future would be quieter, more introverted, passive and withdrawn relative to control children, while at-risk boys would be more prone to externalizing 24 or unpleasant, negativistic, antisocial, irritable and disruptive behaviour. 36,[50][51] Conversely, other studies have reported high levels of physical anhedonia, 33 schizoid traits 9 and withdrawal 38 in boys at risk for schizophrenia relative to control male children. The latter study also reported a bimodal distribution of aggressive behavior in at-risk male children, with a greater prevalence of either absence of or extreme aggression compared to control males.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…There have been suggestions that female children who develop schizophrenia in the future would be quieter, more introverted, passive and withdrawn relative to control children, while at-risk boys would be more prone to externalizing 24 or unpleasant, negativistic, antisocial, irritable and disruptive behaviour. 36,[50][51] Conversely, other studies have reported high levels of physical anhedonia, 33 schizoid traits 9 and withdrawal 38 in boys at risk for schizophrenia relative to control male children. The latter study also reported a bimodal distribution of aggressive behavior in at-risk male children, with a greater prevalence of either absence of or extreme aggression compared to control males.…”
Section: Introductionmentioning
confidence: 85%
“…[50][51] Another limitation is the lack of standardized scales for symptom evaluation in some investigations. 36,51 Therefore, further studies are needed in order to better clarify whether aggressionrelated emotional aspects in at-risk children would indeed represent gender-specific vulnerability markers for more neurodevelopmental, early onset, poor-prognosis forms of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…His formulation of schizophrenia as a loss of common sense suggests a more basic lack of attunement with the shared social world; thus any apparent changes in attitudes, beliefs, and related behavior result from this de-anchoring from commonsense reality. Potentially in support of this view is research suggesting that persons with schizophrenia have felt unable to interact spontaneously with peers even at a young age [21][22][23] . As a result of this gap between oneself and the social world, events and projects that elicit care or concern in others may seem to have little sway over the person with schizophrenia (EAWE 6.2.1, Attitude of indifference, insouciance, lack of concern ).…”
Section: Classic Viewsmentioning
confidence: 73%
“…Também algumas pessoas esquizofrênicas ou com comportamento esquizóide apresentam diferentes graus de incapacidade psicológica e social muito antes do início dos sintomas psicóticos. Estudos retrospectivos, envolvendo esquizofrênicos, têm indicado que um subgrupo destes indivíduos era socialmente incapacitado na infância 29 . Dificuldades de atenção e processamento de informações, mais pronunciadas na puberdade e na adolescência, têm sido relatadas em crianças consideradas de "alto risco" genético para desenvolverem esquizofrenia 30 .…”
Section: Discussionunclassified